TEACHING METHODS OF SENTENCE PARTS TO PRIMARY SCHOOL PUPILS BASED ON INTERNATIONAL ASSESSMENT PROGRAMS (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article analyzes teaching methods of sentence parts to primary school pupils in accordance with the requirements of international assessment programs (PISA, PIRLS, TIMSS). As the central component of syntax, sentence parts play an important role in consolidating students’ grammatical knowledge, comprehending the meaning of texts, and developing skills to express thoughts logically and coherently. The article highlights the effectiveness of applying the 4C model, gamification, and digital learning tools in teaching sentence parts. As a result, students’ communicative competence, critical and creative thinking, collaboration skills, and digital literacy were observed to improve.